Label-free brain tissue imaging using large-area terahertz metamaterials - Lee, Sang-Hun; Shin, Seulgi; Roh, Yeeun; Oh, Seung Jae; Lee, Soo Hyun; Song, Hyun Seok; Ryu, Yong-Sang; Kim, Yun Kyung; Seo, Minah (ELSEVIER ADVANCED TECHNOLOGY, 2020)
Terahertz (THz) imaging technology has shown significant potential for use in biomedical imaging owing to its non-ionizing characteristics by its low photon energy and its ultrabroadband spectral comparability with many molecular vibrational resonances. However, despite the significant advantage of being able to identify biomaterials in label-free configurations, most meaningful signals are buried by huge water absorption, thus it is very difficult to distinguish them using the small differences in optical constants at THz regime, limiting the practical application of this technology. Here, we demonstrate advanced THz imaging with enhanced color contrast by the use of THz field that is localized and enhanced by a nanometer-scale slot array. THz images of a biological specimen, such as mouse brain tissue and fingerprint, on a nano-slot array-based metamaterial sensing chip, which is elaborately fabricated in large-area, show a higher contrast and clearer boundary information in reflectance without any labeling. A reliable numerical solution to find accurate optical constants using THz nanoslot resonance for the quantitative analysis of target bio-specimens is also introduced. Finally, the precise optical properties of real bio-samples and atlas information are provided for specific areas where amyloid beta proteins, known to cause dementia, have accumulated in a mouse brain.
Keywords: ENHANCEMENT; CANCER; MRI